Association of glucose kinase and glucokinase regulatory protein gene polymorphisms with type 2 diabetes mellitus susceptibility in the Asian population: A meta-analysis - Benita Stephen, Sharon; Saravanan, Jayakanthan; Kumar Subbaraj, Gowtham (Chulalongkorn Medical Journal, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a condition in which the body struggles to regulate blood sugar levels. The glucose kinase (GCK) and glucokinase regulatory protein (GCKR) genes play a crucial role in glucose metabolism. GCK produces an enzyme essential for glucose sensing and insulin production, whereas GCKR regulates this enzyme’s activity. Objective: This meta-analysis aimed to investigate the GCK rs1799884 and GCKR rs780094 gene polymorphisms and their association with T2DM in an Asian population. Methods: This study identified articles for two genetic variations (GCK rs1799884 and GCKR rs780094) and assessed their link with type 2 diabetes. We searched online databases, such as Scopus and PubMed, for studies comparing individuals with and without T2DM. Metagenyo was employed as a tool to analyze the data and determine whether these genetic variations increased the risk of developing T2DM. Results: This study suggests that genetic variations in GCK are associated with a higher risk of developing T2DM, regardless of the gene polymorphism in the allelic, recessive, and dominant models. However, analysis of the GCKR rs780094 gene polymorphism and T2DM revealed that these were only associated in the recessive model. Conclusion: This study reveals that the GCK rs1799884 and GCKR rs780094 polymorphisms are associated with a higher chance of developing T2DM in the Asian population.